"I feel it is not enough..." Health providers' perspectives on services for victims of intimate partner violence in Malaysia - Colombini Manuela; Mayhew Susannah; Ali Siti Hawa; Shuib Rashidah; Watts Charlotte (BMC, 2013)
Abstract Background This study explores the views and attitudes of health providers in Malaysia towards intimate partner violence (IPV) and abused women and considers whether and how their views affect the provision or quality of services. The impact of provider attitudes on the provision of services for women experiencing violence is particularly important to understand since there is a need to ensure that these women are not re-victimised by the health sector, but are treated sensitively. Methods In-depth interviews were conducted with 54 health care providers responsible for providing services to survivors of IPV and working in health care facilities in two Northern States in Malaysia. A thematic framework analysis method was employed to analyse the emerging themes. Interviews were coded and managed by using NVIVO (N7), a qualitative software package. Results We found that when providers follow the traditional role of treating and solving IPV as "medical problem", they tend to focus on the physical aspect of the injury, minimise the underlying cause of the problem and ignore emotional care for patients. Providers frequently felt under-trained and poorly supported in their role to help women beyond merely treating their physical injuries. What emerged from the findings is that time shortages may well impact on the ability of medical officers to identify cases of abuse, with some saying that time limitations made it more difficult to detect the real problem behind the injury. However, data from the interviews seem to suggest that time constraints may or may not end up resulting in limited care, depending on the individual interest of medical professionals on violence issues. Conclusions Promoting empathetic health care provision is challenging. More awareness training and sensitisation could help, especially if courses focus on women's needs and strengths and how health providers can validate these and contribute to a longer term process of change for victims of violence. Clear guidance on how to record history of abuse, ask questions sensitively and validate experiences is also important together with training on good communication skills such as listening and being empathetic.